2021
DOI: 10.1038/s41598-021-85297-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of atmospheric rivers on rainfall in New Zealand

Abstract: This study quantifies the impact of atmospheric rivers (ARs) on rainfall in New Zealand. Using an automated AR detection algorithm, daily rainfall records from 654 rain gauges, and various atmospheric reanalysis datasets, we investigate the climatology of ARs, the characteristics of landfalling ARs, the contribution of ARs to annual and seasonal rainfall totals, and extreme rainfall events between 1979 and 2018 across the country. Results indicate that these filamentary synoptic features play an essential role… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 43 publications
3
33
0
Order By: Relevance
“…The rapid transition from dry to wet during seesaw events implies substantial and/or persistent precipitation events. In New Zealand, Reid et al (2021) identified that eight (Christchurch and New Plymouth) and nine (Dunedin) of the top ten rainfall events were associated with an atmospheric river; narrow bands of intense water vapour transport (Newell et al, 1992) that have becoming increasingly associated with extreme precipitation and flooding across New Zealand (Prince et al, 2021;Shu et al, 2021). These same sites (Christchurch, New Plymouth and Dunedin) simultaneously reveal high occurrence of seesaw events in the present work (Fig.…”
Section: Compound and Seesaw Events Manuscript Submitted To The Journ...supporting
confidence: 65%
“…The rapid transition from dry to wet during seesaw events implies substantial and/or persistent precipitation events. In New Zealand, Reid et al (2021) identified that eight (Christchurch and New Plymouth) and nine (Dunedin) of the top ten rainfall events were associated with an atmospheric river; narrow bands of intense water vapour transport (Newell et al, 1992) that have becoming increasingly associated with extreme precipitation and flooding across New Zealand (Prince et al, 2021;Shu et al, 2021). These same sites (Christchurch, New Plymouth and Dunedin) simultaneously reveal high occurrence of seesaw events in the present work (Fig.…”
Section: Compound and Seesaw Events Manuscript Submitted To The Journ...supporting
confidence: 65%
“…Although their importance diminishes away from the west coast and topographic forcing associated with the Southern Alps, ARs were shown to remain critical to precipitation climatology across a series of locations around New Zealand. In subsequent studies, both Reid et al (2021) and Shu et al (2021) have found a similarly dominant role of ARs for extreme precipitation events across New Zealand. Furthermore, these broad characteristics of New Zealand AR climatology are reflected in more geographically focussed studies within New Zealand, and from precipitation to river flows and the cryosphere.…”
Section: Introductionmentioning
confidence: 90%
“…(2021) and Shu et al . (2021) have found a similarly dominant role of ARs for extreme precipitation events across New Zealand. Furthermore, these broad characteristics of New Zealand AR climatology are reflected in more geographically focussed studies within New Zealand, and from precipitation to river flows and the cryosphere.…”
Section: Introductionmentioning
confidence: 90%
“…Generally, 15–35% of the extremes are associated with the dominant WTs identified in Figure 15b. This could be due to interferences with other rain‐bearing systems or mechanisms not necessarily discriminated by the WTs, like atmospheric rivers (recently shown to be involved in many major rain events in ANZ: Prince et al ., 2021; Reid et al ., 2021; Shu et al ., 2021), or ex‐tropical cyclones (Lorrey et al ., 2014b). Three main regions show slightly larger values, denoting a stronger relationship between WTs and intense or precipitation extremes: (a) the Fiordland region, southwest of the South Island; (b) the northern part of the Southern Alps in the South Island; (c) the central‐western part of the North Island, around the volcanic peak of Mount Ruapehu.…”
Section: Daily Precipitation and Temperature Extremesmentioning
confidence: 99%